Phase slip process and charge density wave dynamics in a one dimensional conductor - N. Habiballah; M. Zouadi; A. Arbaoui; M. Qjani; J. Dumas (Results in Physics, 2017)
In this paper, we study the phase slip effect on the charge density wave (CDW) dynamics in a one-dimensional conductor in the weak pinning limit. A considerable enhancement of JCDW is observed in the presence of phase slips. In addition, a spatial dependence of the CDW current density JCDW is also studied showing that a decrease of JCDW with distance from the current contact occurs. The results are discussed in terms the relationship between additional phase slips and the mobility of phase dislocations nucleated at electrical contacts. Keywords: Phase slip process, Charge density wave, Phase dislocation, Fukuyama-Lee- Rice model